Study on vibration threshold of the elevator in Vietnam - Luu, Thanh Tung (Journal of Technical Education Science, 2018)
Nowadays, elevators are installed for most of buildings and they are familiar with everyone in modern life. Some domestic elevators make passenger nervous because of vibration and noise. Thus, the elevators are required smoother and quieter. However, elevator manufacturing factories have no methods and equipments to measure vibration in elevators. In reality, the installer only listen to the sound and feel sway and then assess the comfort subjectively. Therefore, this paper introduces a method using a3-axis accelerometer to measure the vibration of elevators in 3 axes X Y Z. However, these vibration signals are difficult to compare among other elevators. Thus, a methodology called Fast Fourier Transform (FFT) inverts these data in time domain into frequency domain to illustrate vibration spectrum. This spectrum will be compared with standard one built by the manufacturer. In this paper, the standard spectrum of well-known elevator manufacturers such as Kone, Schindler etc. will be introduce for reference of Vietnamese elevator manufacturers.